Distribution Matters: The Reverse Robin-Hood Macroeconomic Effects - Alonzi, Loreto Peter; Drougas, Anne; Condon, Daniel (Journal of Applied Business and Economics, 2018)
This paper examines income distribution’s impact on aggregate demand. Income distribution is introduced by replacing consumption as a function of aggregate income with consumption as the sum of two consumptions: a high income group’s and low income group’s. Notably the high income group’s MPC is assumed to be less than the lower income group’s. Analysis reveals two key results. As the high income group’s proportion of income rises: (1) aggregate demand falls and (2) autonomous spending changes cause smaller aggregate demand shifts. A reduced multiplier is the key. Empirical work supports the assumption that the high income group’s MPC is less than the low income group’s.